ANTIBIOTIC PROPHYLAXIS IN ABDOMINAL SURGERY – COMPLIANCE WITH INTERNATIONAL GUIDELINES - Veličković, Jelena; Sredić, Suzana; Radovanovic Spurnic, Aleksandra; Lazić, Igor; Palibrk, Ivan; Mioljević, Vesna; Ostojić, Slavenko (Srpski medicinski časopis Lekarske komore, 2022)
Introduction. Antibiotic prophylaxis (AP) in surgery is an important measure that contributes to the prevention of surgical site infection. International and national guidelines provide clear recommendations for the proper implementation of antibiotic prophylaxis. However, many studies indicate poor compliance in many health care centers. Aim: Our study aimed to determine the level of compliance in the application of antibiotic prophylaxis in abdominal surgery with the guidelines. Materials and methods. The retrospective study included all patients which were operated on at the Clinic for Digestive Surgery of the University Clinical Center of Serbia (UCCS), during the period January - March 2019 (270 patients). Medical records provided information about the type of surgery, the choice of antibiotic, the time of application, the route of administration, the need for redosing, the duration of antibiotic prophylaxis administration, as well as the presence of drug allergies. The collected data were analyzed by descriptive and analytical statistics (χ2 test). Results. During the study period, 270 patients were operated on at the Clinic for Digestive Surgery, of whom 227 (84.1%) received antibiotic prophylaxis. Cefazolin, an antibiotic recommended for most abdominal surgeries, was administered to only 17 (6.3%) patients. The majority of patients (64.4%) received antibiotic prophylaxis within 30 minutes of the beginning of surgery. The duration of antibiotic prophylaxis of up to 24 hours after the operation was applied in 13.1% of patients. Conclusion. Compliance with the guidelines was low, while full compliance with the recommendations for antibiotic prophylaxis was achieved only with regards to the route of antibiotic administration.